Application of Legal Protection for Tourists Who Have Losses Due to Force Majeure - I Putu Martha Kresna Raditya (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2019)
Tourism activities are growing rapidly with technological advances. Tourists who come not only from domestic but also from overseas. The success of a tourist attraction is influenced by the tourism executor that is the provider of tourist services and tourists. This is inseparable from the service factor provided by the tourism service providers. Arrangements set forth in the form of laws governing the regulation of tourism is needed to have both from tourist and tourist service providers. In the tour, certainly will not be separated from the factors that disadvantage the tourism executor. The aims of reserach is to know form of protection for tourists who have losses due to force majeure and accountability of tourist service providers to tourists in the event of force majeure. The method of this research is normative research by examining library materials such as legislation, books or literature, as well as dictionaries or encyclopedias. The approach taken in this study is the legislative approach and the conceptual approach. The legal material analysis techniques used are description, systematization, interpretation, and argumentation. The force majeure in his theory frees the solicitor to be free from responsibility to tourists. At this writing, the author tries to discuss about the application of legal protection for tourists who experiencing losses due to force majeur.